THE COMPARATIVE ANALYSIS OF THE LABOR MARKET INDICATORS IN A SELECTED GROUP OF EU COUNTRIES - M. Balcerowicz-Szkutnik (Вісник Київського національного університету імені Тараса Шевченка. Серія Економіка)
The paper presents, in a synthetic way, the problems of dynamics of labour market of “ten new member states” that joined EU in 2004, focusing mainly on the level of employment and taking into account the lines of business and age employees. The time range from 2000 to 2011, selected for the purpose of the analysis, includes the years that directly preceded and directly followed the accession to the EU and aims at determining possible changes in parameters that characterise the labour market in selected states.